Robo-AO and SOAR High-Resolution Surveys of Exoplanet Hosting Stars - Ziegler, Carl; Law, Nicholas; Baranec, Christoph; Riddle, Reed; Tokovinin, Andrei (Frontiers in Astronomy and Space Sciences, 2021)
In the past decade, space-based transiting exoplanet discovery missions have delivered thousands of potential planet-hosting systems. Each of these needs to be vetted and characterized using follow-up high-resolution imaging. We perform comprehensive imaging surveys of the candidate exoplanets detected by the Kepler and TESS missions using the fully autonomous Robo-AO system and the largely autonomous SOAR speckle imaging system. The surveys yielded hundreds of previously unknown close binary systems hosting exoplanets and resulted in verification of hundreds of exoplanet systems. Evidence of the interaction between binary stars and planetary systems was also detected, including a deep deficit of planets in close binary systems.